1990
DOI: 10.1177/030089169007600607
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal Breast Carcinoma. Review of a Multicenter Series of 350 Cases

Abstract: A multicenter series of 350 intraductal breast cancers (DCIS) is reported. Mammography was the most sensitive test but suspicion arose only at palpation in 13% of cases whereas in 10% of cases biopsy was recommended for a benign lesion and DCIS was an unexpected finding. Mammography, physical examination and cytology must be combined to achieve optimal sensitivity. Systematic biopsy of apparently benign masses would increase DCIS detection rates but the cost-effectiveness of such a policy is questionable. A tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Most cases of DCIS are detected by mammography, which is now the most sensitive diagnostic procedure available 15 . In our study, 94% of DCIS were mammographically detectable.…”
Section: Discussionsupporting
confidence: 54%
“…Most cases of DCIS are detected by mammography, which is now the most sensitive diagnostic procedure available 15 . In our study, 94% of DCIS were mammographically detectable.…”
Section: Discussionsupporting
confidence: 54%
“…36 Retrospective studies on patients with DCIS treated with excision alone have reported local recurrence rates between 6% and 63%. [37][38][39][40][41][42][43][44] Recurrence rates were lower (6% to 21%) for patients with DCIS who received postoperative radiotherapy. 24,38,[45][46][47][48][49][50][51] Studies on mammographically detected DCIS treated with wide local excision and radiotherapy have reported local recurrence rates between 4% and 18%.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical outcomes for localized disease are subject to considerable variations. Five-year overall survival is considered to be between 49% and 67% [ 3 , 4 , 16 , 22 , 34 , 62 , 69 , 70 ]. These ranges are due to the heterogeneity of histological subtypes and treatment protocols analyzed in each study.…”
Section: Discussionmentioning
confidence: 99%